The implementation of nutrition improvement programs for underweight children, wasting and stunting in the Department of Health, Central Buton district, Southeast Sulawesi - Nur Wulandari; Ani Margawati; Zen Rahfiludin (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Health status can affect the Human Development Index (HDI) of a country. To improve the quality of human resources, the Indonesian Government has applied various policies, such as the nutrition improvement program, since there are still lots of toddlers suffering from underweight, wasting dan stunting. Even one out of three toddlers in Indonesia were detected stunting.Objectives: This study described the implementation of a nutrition improvement program for toddlers in the Central Buton District Health Office.Materials and Method: This was a qualitative study that involved ten informants. Three of those informants are nutritionists in the District Health Office, Head of Public Health Department, Head of NutritionDepartement. Also, two nutrition workers in primary healthcare centers and two mothers of malnourished toddlers.Results: These findings showed that in terms of input, trained human resources on nutrition were lacking, and the budget for the nutrition improvement program was inadequate. While, in the process, all implementors had done very well, although they still had no collaboration across sectors. In the output aspect, the health status of underweight, wasting, and stunting toddlers improved. Also, monitoring and evaluation were conducted on toddlers registered at the integrated service posts in 2018.Conclusions: There were still constraints on the input, process, and output aspects, even though there was an increase in the nutritional status of children under five, but nutrition problems for children under five in Central Buton Regency were still high.